A ação coletiva e seus sentidos: narrativas de vida de mulheres em contextos rurais no Seridó Paraibano - Torres, Ewerton José de Medeiros (2019)
This thesis is about valuing the tales told by women oppressed by sexism and patriarchy, but who find strength by gathering in groups. The main goal is to find out the meaning behind those groups, and the target was the women from three counties of the Seridó‘s Paraíba. The techniques chosen for this thesis were their life story, the stories they told, along the Weberian methodology to create their own narrative. The tools used to collect the data were scripted interviews, observation, as well as the monitoring of the group's dynamics, their timelines and the construction of even smaller groups within their own. Each group has its own agenda and a total of fifteen women were interviewed. The findings lead to the conclusion that there are two main groups in their dynamics: one is more focused on the family and their feelings and the other one, who fights to guarantee their rights, and also that the main reason why these women get together is to support each other, work and make a living in the Seridó region